2020
DOI: 10.18280/ts.370110
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Antilogarithmic Converter by Using Correction Scheme for DSP Processor

Abstract: Digital Signal Processing (DSP) applications demand error-free and compact hardware architecture of arithmetic operations. A logarithmic operation provides an efficient option in place of binary arithmetic. In this paper, it is suggested that 11-region and 17-region error correction schemes for developing an efficient antilogarithm converter. It is used for developing the most accurate and compact logarithm multiplier which is used in the DSP processor. Implementations of reported and proposed designs are inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In 2019, Durgesh and his research team suggested 16 regions based "error correction scheme" for "antilogarithm converter" [22]. In 2020, Durgesh and his research team suggested multi regions "error correction scheme" "antilogarithm converter" for DSP processor [23]. For error minimization circuit in antilogarithm converter when it is increases the number of regions, hardware cost increasing and errors are decreasing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2019, Durgesh and his research team suggested 16 regions based "error correction scheme" for "antilogarithm converter" [22]. In 2020, Durgesh and his research team suggested multi regions "error correction scheme" "antilogarithm converter" for DSP processor [23]. For error minimization circuit in antilogarithm converter when it is increases the number of regions, hardware cost increasing and errors are decreasing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The overall converter design needs only 50 slices representing just 0.32% of the used FPGA chip capacity. In Table 5, the obtained results are compared with the reference conventional approximation methods [6] and very fast shift-and-add methods [20]. Latency of the circuit, or the time from input to output as a performance measure, is very circuit-dependent.…”
Section: Design Of An Lns To Flp Convertermentioning
confidence: 99%
“…In the considered reference design, the FPGA Virtex II was used, which is an older product line of the Xilinx FPGA chips. Previous converters are realized on 65 nm full customizable CMOS technology with latency under 1 ns [20]. For our implementation, a 28-nm prefabricated structure of FPGA Artix-7 was used.…”
Section: Design Of An Lns To Flp Convertermentioning
confidence: 99%
See 2 more Smart Citations